Identification of Lsd1-interacting non-coding RNAs as regulators of fly oogenesis. - Shao, T.L.; Ting, R.T.; Lee, M.C. (Cell reports, 2022)
Lysine-specific demethylase 1 (Lsd1) plays a key role in balancing cell proliferation and differentiation. Lsd1 has been recently reported to associate with specific long noncoding RNAs (lncRNAs) to account for oncogenic gene expression in cancer cells. However, how lncRNA-Lsd1 interplay affects cell-specific differentiation remains elusive in vivo. Here, through Lsd1 specific RNA immunopecipitation sequencing (RIP-seq) experiments, we identify three long hairpin RNAs as Lsd1-interacting non-coding RNAs (LINRs) from fly ovaries. Knocking out LINR-1 and LINR-2 affects fly egg production, while each of the LINR deletion mutant females produce eggs with reduced hatch rate, indicating important functions of LINRs in supporting oogenesis. At the cellular level, LINR-2 regulates the differentiation of germline stem cells and follicle progenitors likely though modulating the expression and function of Lsd1 in vivo. Our identification of ovarian LINRs presents a physiological example of dynamic lncRNA-Lsd1 interplay that regulates stem cell/progenitor differentiation.